Peran Organizational Citizenship Behavior Dalam Memediasi Pengaruh Transformational Leadership Terhadap Innovative Work Behavior (Studi Pada Dinas Kesehatan Kota Bandung) - Maria Apriliyanti Ningrum; Ani Surtiani Surtiani; Ginanjar Wira Saputra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The government encourages innovation in local governments. The success of organizational innovation is certainly inseparable from the innovative work behavior of its employees. To improve innovative work behavior, many factors influence. The purpose of this study is to determine the role of organizational citizenship behavior that mediates the influence of transformational leadership on innovative work behavior. Sample collection is carried out by random sampling and is cross sectional. Using the Slovin formula, a sample of 83 people from a population of 847 was obtained. Based on the test results, it was found that Transformational leadership (β = 0.632; t = 5.654; p-values = 0.000), had a positive and significant effect on innovative work behavior, Transformational leadership (β = 0.734; t = 18.946; p-values = 0.000), positive and significant effect on organizational citizenship behavior, Organizational citizenship behavior (β = 0.761; t = 7.339; p-values = 0.000), positive and significant effect on innovative work behavior and Organizational citizenship behavior (β = 0.558; t = 7.746; p-values = 0.000), as mediator variables have a positive and significant effect on the causal relationship between transformational leadership with innovative work behavior. The magnitude of the model's prediction power with an R-Square score, which is 0.743 for innovative work behavior and 0.538 for organizational citizenship behavior. Thus, transformational leadership has a positive effect on innovative work behavior both directly and through organizational citizenship behavior. Keywords: Innovative Work Behavior, Organizational Citizenship Behavior, Transformational Leadership